Concurrent hyperbaric oxygen therapy and intratympanic steroid application as salvage therapy after severe sudden sensorineural hearing loss. Issue 3 (11th February 2016) - Lamm, Hans; Müller‐Kortkamp, Claus; Warnecke, Athanasia; Pohl, Friederike; Paasche, Gerrit; Lenarz, Thomas; Stolle, Stefan R. O.
Key Clinical Message: Concurrent hyperbaric oxygen therapy (HBOT) and intratympanic steroid application (ITS) are beneficial as salvage therapy for therapy‐refractory sudden sensorineural hearing loss (SSNHL). The findings encourage further research on the treatment of noise‐induced and idiopathic SSNHL with concurrent use of HBOT and ITS respecting also patients with long‐term or therapy‐refractory SSNHL. Abstract : Concurrent hyperbaric oxygen therapy (HBOT) and intratympanic steroid application (ITS) are beneficial as salvage therapy for therapy‐refractory sudden sensorineural hearing loss (SSNHL). The findings encourage further research on the treatment of noise‐induced and idiopathic SSNHL with concurrent use of HBOT and ITS respecting also patients with long‐term or therapy‐refractory SSNHL.